2012
DOI: 10.1089/dna.2011.1294
|View full text |Cite
|
Sign up to set email alerts
|

The Role ofp73G4C14-to-A4T14 Polymorphism in the Susceptibility to Cervical Cancer

Abstract: Several reports have suggested the importance of p73 polymorphisms in tumor behavior. We investigated the role of a p73 gene polymorphism in the susceptibility to cervical lesions in a southwestern European population. Peripheral blood samples were obtained from Radiotherapy and Gynaecology Departments of Portuguese Institute of Oncology (Porto, Portugal), from 1998 to 2002. We analyzed the p73 cytosine thymine polymorphism in peripheral blood DNA of 176 healthy donors, 38 high-grade squamous intraepithelial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Furthermore, a previous study observed that the AT variant was associated with significantly decreased risk of cervical cancer compared with p73 GC homozygotes (37). The results of the present study are consistent with Craveiro et al (35) and demonstrated that individuals carrying the p73 G4C14-to-A4T14 AT/AT genotype are associated with a higher risk of cervical cancer than individuals with the GC/GC genotype in a Chinese population. In addition, a significant association was observed between p73 G4C14-to-A4T14 SNP genotypes and tumor size in patients with cervical cancer (P=0.014; χ 2 =8.607).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, a previous study observed that the AT variant was associated with significantly decreased risk of cervical cancer compared with p73 GC homozygotes (37). The results of the present study are consistent with Craveiro et al (35) and demonstrated that individuals carrying the p73 G4C14-to-A4T14 AT/AT genotype are associated with a higher risk of cervical cancer than individuals with the GC/GC genotype in a Chinese population. In addition, a significant association was observed between p73 G4C14-to-A4T14 SNP genotypes and tumor size in patients with cervical cancer (P=0.014; χ 2 =8.607).…”
Section: Discussionsupporting
confidence: 93%
“…However, the number of these studies is limited. It has been demonstrated that patients with cervical cancer carrying the p73 AT allele in a southwestern European population have a two-fold increased susceptibility of developing high-grade squamous intraepithelial lesions (35). By contrast, an unconditional logistic model performed risk estimation for each p73 genotype and identified a possible association between the p73 A4T14 variant and risk of cervical cancer in a Japanese population (P=0.053; OR = 1.57; 95% CI = 0.99-2.48) (36).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, gene polymorphisms of DNA repair factors are therefore obvious candidates for determinants of repair capacity and chemotherapy efficacy (Sancar, 1995). Moreover, the functional variants caused by SNPs in genes encoding drugmetabolizing enzymes, transporters, ion channels, drug receptors, cell cycle proteins and DNA repair are known to be associated with individual variation in survival, drug responses, and toxicity (Henson et al, 2006;Costa et al, 2008;Nogueira et al, 2010;Catarino et al, 2008;Craveiro et al, 2012;Santos et al, 2006;Medeiros et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have reported a decreased risk in lung [29] and head and neck cancers [19]. In addition, many studies reported no association in breast [7, 9, 10], cervical [11], colorectal [13, 14, 16], endometrial [17], head and neck [13, 18, 19, 21, 22], gastric [13, 25], ovarian [36], melanoma [35], and lung [30, 31, 33] cancers (Table 4). Recent meta-analyses have shown that the p73 DNP is associated with various cancer risks in general [3841].…”
Section: Discussionmentioning
confidence: 99%